Reproduksibilitas Biomarker Radiomics pada PET Molecular imaging: A Systematic Literature Review - ADITYA PRATAMA PUTRA (Poltekkes Kemenkes Semarang, 2026)
Background: Radiomics has emerged as a promising quantitative approach in PET molecular imaging; however, its clinical translation remains limited by concerns regarding feature reproducibility under varying technical conditions. This systematic literature review aimed to identify and synthesize the main technical factors influencing the reproducibility of PET radiomic biomarkers. Methods: A systematic literature Review was conducted using the Scopus database with the search strategy TITLE-ABS-KEY (radiomics AND (PET OR PET/CT) AND (reproducibility OR